2022
DOI: 10.1590/2317-6431-2021-2615
|View full text |Cite
|
Sign up to set email alerts
|

Produção da fala de crianças e adolescentes de um programa de reabilitação auditiva

Abstract: RESUMO Objetivo caracterizar a produção da fala de crianças e adolescentes usuários de aparelho de amplificação sonora individual (AASI) ou implante coclear (IC) de um programa de reabilitação auditiva. Métodos estudo observacional transversal. Foram analisadas amostras de fala de 15 participantes de um programa de reabilitação auditiva, que consistiam na prova de fonologia do ABFW (ABFW - Teste de Linguagem Infantil nas Áreas de Fonologia, Vocabulário, Fluência e Pragmática) e na fala espontânea, adaptada d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Research [2] analyzed the speech of 15 children and adolescents with moderate bilateral sensorineural hearing loss who have used PSAPs for more than 4 years and underwent auditory rehabilitation. They observed that the individuals who participated in their research achieved good speech intelligibility, proving that while oral communication is a challenge for children with hearing impairment, if their auditory skills are stimulated, their speech production becomes more adequate and effective than with the use of a PSAP alone.…”
Section: Introductionmentioning
confidence: 99%
“…Research [2] analyzed the speech of 15 children and adolescents with moderate bilateral sensorineural hearing loss who have used PSAPs for more than 4 years and underwent auditory rehabilitation. They observed that the individuals who participated in their research achieved good speech intelligibility, proving that while oral communication is a challenge for children with hearing impairment, if their auditory skills are stimulated, their speech production becomes more adequate and effective than with the use of a PSAP alone.…”
Section: Introductionmentioning
confidence: 99%